Manajemen Hubungan Pemustaka Berbasis CRM sebagai Kunci Kepercayaan dan Loyalitas di Perpustakaan Vokasi UGM - Kusuma Dewandaru, Dyah Ayu; Rospitasari, Marina; Puspasari, Lusi (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
The rapid development of information technology (IT) often correlates with a decline in academic library visits. However, the Vocational School (SV) Library at Gadjah Mada University (UGM) reported a significant increase in visitor and borrower numbers post-COVID-19. This phenomenon prompted a study to examine the effect of Customer Relationship Management (CRM) on user trust and the subsequent effect of trust on user loyalty. This quantitative study used a Path Analysis within a Structural Equation Model (SEM), with data collected from 357 SV UGM students. The analysis showed that CRM had a positive and significant effect on user trust ($β = 0.902$; $p=0.001$), explaining 81.4% of the trust variability ($R^2=0.814$). This success was supported by five CRM indicators, including internal capabilities and customer interaction. Furthermore, user trust significantly influenced user loyalty ($β = 0.849$; $p=0.001$), explaining 72% of the loyalty variability ($R^2=0.720$). Loyalty is built through the three factors of trust: librarian ability, benevolence, and integrity. High loyalty was evident in the frequent visits reported by users. In conclusion, CRM enhances trust, which ultimately fosters user loyalty. Libraries are advised to continually assess user needs to provide satisfactory services and maintain this trust and loyalty.